2005
DOI: 10.1021/ic050147x
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Structures and Magnetic Properties of Halide-Bridged, Face-to-Face Bis-Nickel(II)-Macrocyclic Ligand Complexes:  Ligand-Mediated Interchanges of Electronic Configuration

Abstract: Dramatic differences are found between the ambient and 100 K X-ray structures of [L(2)Ni2Br2](ClO4)2 (L(2) = alpha,alpha'-bis{(5,7-dimethyl-1,4,8,11-tetraazacyclotetradeca-6-yl)-o-xylene), in which the bromide-bridged, bimetallic, macrocyclic ligand complexes of nickel(II) are held face-to-face and in which each bimetallic complex has a net triplet spin multiplicity. The ambient structure of this complex consists of very highly ordered, infinite chains of alternating R and S isomers in which the identical Ni(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 57 publications
(93 reference statements)
1
28
0
Order By: Relevance
“…In any case, metal-ligand interactions are typically more intense than electrostatic/hydrogen-bond interactions and afford the formation of more stable receptor/anion complexes. [23] More recently,w eh ave studied the behaviour of the [Ni II 2 (bicyclam)] 4 + complex as an anion receptor in DMSO, with special reference to the effect of anion inclusion on the Ni II -to-Ni III oxidation processes taking place at the two metal centres. Such an inconvenience can be removed by using metallocyclam subunits: in particular, transition-metali ons, if encircled by the 14-membered cyclic tetraamine cyclam, achieve an extreme inertness towards demetallation, even under severe conditions (due to the kinetic macrocyclic effect).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, metal-ligand interactions are typically more intense than electrostatic/hydrogen-bond interactions and afford the formation of more stable receptor/anion complexes. [23] More recently,w eh ave studied the behaviour of the [Ni II 2 (bicyclam)] 4 + complex as an anion receptor in DMSO, with special reference to the effect of anion inclusion on the Ni II -to-Ni III oxidation processes taking place at the two metal centres. Such an inconvenience can be removed by using metallocyclam subunits: in particular, transition-metali ons, if encircled by the 14-membered cyclic tetraamine cyclam, achieve an extreme inertness towards demetallation, even under severe conditions (due to the kinetic macrocyclic effect).…”
Section: Introductionmentioning
confidence: 99%
“…Dinickel(II) complexes of bicyclam were investigated for their uniquem agnetic properties by Ito and co-workers, [21,22] and later,v ery thoroughly,b y Endicott and co-workers. [23] More recently,w eh ave studied the behaviour of the [Ni II 2 (bicyclam)] 4 + complex as an anion receptor in DMSO, with special reference to the effect of anion inclusion on the Ni II -to-Ni III oxidation processes taking place at the two metal centres. [24] Herein, we report ac omplete thermodynamic investigation on the interaction of the [Cu II 2 (bicyclam)] 4 + receptor with anions in pure water.T he [Cu II (cyclam)] 2 + subunit exhibits a defined tendency to bind furtherl igands( e.g.,a nions) to achieve five coordination; [25] ac ircumstancet hat should favour anion inclusion inside the intermetallic space of [Cu II 2 (bicyclam)] 4 + .A nion binding equilibriah ave been investigated through isothermal titration calorimetry (ITC), which allowed the determination of association constants (and DG8), as well as of enthalpy, DH8,a nd entropy contributions, TDS8.I t has been shown that knowledge of these thermodynamic quantities may allow the interpretation of the solutions tability of the anion complexes in terms of inner effects (receptoranion bonding, conformational rearrangement of the framework of the receptor) and outer effects (releaseo fw ater molecules to the solution due to anion and receptor dehydra-tion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it would constitute an exciting research topic, it will encounter difficulties, because in many instances the magnetic behavior has gone unreported, and often the high-or low-spin nature of a complex is deduced from interatomic distance criteria without magnetic or spectral evidence. [37] Nevertheless, our shape analysis has allowed us to identify cases of significantly dissociated octahedra for which a lowspin behavior has been reported (see entries PTOCNI10 [38] and LATXOU [39] in Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…For the bromo-bridged Ni complex of the macrocyclic ligand ␣,␣ -2-bis{(5,7-dimethyl-1,4,8,11-tetraazacyclotetradeca-6-yl)-o-xylene} a phase transition between room temperature and 100 K with marked changes both in the structure and in the magnetic properties has been observed [50].…”
Section: Chains From Corner-sharing Octahedramentioning
confidence: 99%